La mise en tourisme de la ville : de la transformation de l’espace à la résilience de la destination - Boualem Kadri; Cyril Martin; Benoit Duguay (Études Caribéennes)
The setting in tourism constitutes today a mode of development sought at the political and professional levels but still little analyzed within the scientific community. Many Cities are important destinations, and are particularly subject to a dynamic of multiple transformations (architectural, social and capitalistic), and thus would be perceived as an object and a model for understanding the issues of today’s society, including the resilience capacity faces various phenomena (climatic, epidemiological, socio-political). The tourist activity through the setting in tourism of the territories becomes then an object of observation and analysis of the resilience of this destination. How to apprehend the process of tourism for cities and metropolises subject to continuous adaptation, especially as a tourist destination? Tourism, in the case of a city/metropolis, would move from a perspective centred on the transformation of space to that of a dynamic project, renewal and therefore resilience of the destination. The process of tourism will be approached from two prospects: a first more conceptual and semantic concept of tourism used by various authors; a second, more applied, will examine the actions and representations of actors involved in the process of tourism, according to three case studies.